2019
DOI: 10.1055/s-0039-1685451
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety among Patients with Atraumatic Lateral Epicondylitis and Ulnar-Sided Wrist Pain

Abstract: Background Ulnar-sided wrist pain (UWP) and lateral epicondylitis (LE) are common disorders that can be difficult to treat. Depression and anxiety have been shown to modify patient symptoms, disability and pain. Questions/Purposes The purpose of our study was to quantify the prevalence of depression and anxiety among patients with LE or UWP. A secondary aim was to determine if these patients report higher levels of pain upon presentation and if they are more likely to require occupational therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…We used the SCL-90-R test which is rarely used in psychiatry but it is commonly helpful in other medical disciplines or investigations to evaluate several psychiatric disorders. Patients with underlying diagnosis of depression had significantly higher pain scores similar to what Pensak et al [17] reported.…”
Section: Discussionsupporting
confidence: 82%
“…We used the SCL-90-R test which is rarely used in psychiatry but it is commonly helpful in other medical disciplines or investigations to evaluate several psychiatric disorders. Patients with underlying diagnosis of depression had significantly higher pain scores similar to what Pensak et al [17] reported.…”
Section: Discussionsupporting
confidence: 82%